If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8g + 7 = -1g + 63 Reorder the terms: 7 + -8g = -1g + 63 Reorder the terms: 7 + -8g = 63 + -1g Solving 7 + -8g = 63 + -1g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'g' to each side of the equation. 7 + -8g + g = 63 + -1g + g Combine like terms: -8g + g = -7g 7 + -7g = 63 + -1g + g Combine like terms: -1g + g = 0 7 + -7g = 63 + 0 7 + -7g = 63 Add '-7' to each side of the equation. 7 + -7 + -7g = 63 + -7 Combine like terms: 7 + -7 = 0 0 + -7g = 63 + -7 -7g = 63 + -7 Combine like terms: 63 + -7 = 56 -7g = 56 Divide each side by '-7'. g = -8 Simplifying g = -8
| 70=6x-14 | | 7j-4=3j-28 | | 10e-4=4e-10 | | 2a+4=-3a-36 | | -2q+6=3q-24 | | 2x-1=-x-28 | | 6h-4=h-9 | | 9y-1=5y+15 | | 12+8=5d+57 | | 7(3g+8)/4=35 | | 8-32x+27x-3=0 | | 4(x-5)=-1.6 | | 12d+8=8d+16 | | 13=5c-9 | | 9e-7=28.1 | | 8(x-2)=26.4 | | 2(3y-6)=-18 | | 2(7v-4)=-22 | | 3(4k-4)=60 | | 4(6u-4)=152 | | 3(5t+2)=-84 | | 5(4q+3)=-145 | | 8e-7=17 | | 16.2=2c-2 | | 5(4x-4)=-40 | | 3(4f+1)=-21 | | 5(3s-2)=-145 | | 6e-4=14 | | 9(a+3)=108 | | 2p=19.4 | | -3n+5=20 | | 6=3c-9 |